(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
Microwaves in the frequency range of 30–300 GHz are called millimetre waves (MMWs) because the wavelength in vacuum belongs to the interval of 1–10 mm. There is a substantial number of studies showing biological effects of MMWs at nonthermal intensities, but there is not yet explanation of the interaction phenomena of Extremely High-Frequency Electromagnetic Fields with alive objects, which is very important for diagnosis and therapy.